The Writing of the Biography of Muhammad - Barmawy Munthe (Al-Jami'ah: Journal of Islamic Studies, 1994)
Andrew Rippin says that, "biography   is a powerful mirror   for the reflection of the ideals, as well as the standards, of the age in which it is written, and thus may be seen to reflect the contemporary situation of its authors in the very construction of the facts which the work   intends to records".'  Also, biography   tend to idealize a person or his life and often serves a medium for expressing the ideas and ideals of the writer. Muhammad  has been a man about  whom  many studies  have been done. Discussion   on Muhammad   reflects   the image and   inspiration of writers whether they be medieval Muslims and Christians or modem   Muslims and modern scholars. Depending on the time to which different writers belong, the writing of biography of Muhammad has different trends which depend on the writer's backgrounds and interest or for different purposes   using different starting points. This paper examines some scholars' inequality ideas and ideals and their illustration on Muhammad on the different times they belong. It seems that medieval Muslim writers have discussed the biography of Muhammad in a mythical and apologetic view.  Among them that be becomes extraordinarily significant; as a Holy Prophet, as the Messenger of God and as the example of the ideal practice of the teachings of Islam.  Ibn Ishaq (702-767), in his The Life of Muhammad, says that being a messenger of God. Muhammad was a statesman and a great diplomat who established a good relationship with the Jews of Madinah and was victorious in many maghazis (wars) with the help of supernatural power. Ibn Ishaq provides  a richly embellished life of Muhammad   which concentrates on the many miracles which God made him perform, especially those in the early part of his life.